Properties of Lunar Regolith on the Moon's Farside Unveiled by Chang'E‐4 Lunar Penetrating Radar. Issue 6 (7th June 2021) - Dong, Zehua; Fang, Guangyou; Zhou, Bin; Zhao, Di; Gao, Yunze; Ji, Yicai
Abstract: The complex thermal history of the Moon leads to an unequal distribution of volcanic products between the lunar nearside and the farside. So far, no lunar materials have been sampled from the Moon's farside and no detailed properties of lunar regolith on the farside have been detected before. On January 3, 2019, Chang'E‐4 (CE‐4) touched down onto the Von Kármán crater on the Moon's farside. CE‐4 Lunar Penetrating Radar (LPR) onboard the Yutu‐2 rover is the first surface radar on the Moon's farside. Here we show the subsurface structure and properties of regolith materials at the landing region with LPR data during the first five lunar days. The thickness of lunar regolith is constrained as ∼12 m, much thicker than that at Chang'E‐3 (CE‐3) landing site, which is expected since CE‐3 landed on lunar maria. The relative permittivity of lunar surface (<30 cm) at CE‐4 landing region is identified to be 2.35 ± 0.20. The loss tangent and TiO2 + FeO content of the regolith materials layer (0–∼12 m) are constrained to be ( 4.4 ± 0.5 ) × 10 − 3 and 11.6 ± 1.1 wt.%, respectively, much lower than those at CE‐3 landing site. It indicates that local surface materials possess less attenuation for radiowave, in accordance with the greater penetrating depth of CE‐4 LPR than that of CE‐3 LPR. Furthermore, the results also prove that the growth rate of lunar weathered regolith successively declines over time and the growth rate of lunar regolith on the Moon's farside may well be higher than that on the nearside due to the more frequent meteorite impacts. Plain Language Summary: Lunar regolith (informally called the lunar soil) is the uppermost material on the lunar surface. It preserves vital clues about geology and impact history of the Moon. Although numerous missions to the Moon have landed on the nearside, so far, no lunar materials have been sampled from the Moon's farside. In 2019, China's Chang'E‐4 (CE‐4) spacecraft softly landed on the farside of the Moon for the first time and deployed its rover, Yutu‐2. The Lunar Penetrating Radar (LPR) onboard Yutu‐2 can transmit electromagnetic pulses to detect the lunar subsurface structure and properties of the regolith. The relative permittivity, loss tangent and TiO2 + FeO content of lunar regolith materials at landing site are constrained with LPR data in this paper. The results indicate that the farside may be bombarded more frequently, leading to different regolith accumulation rates on the lunar nearside versus farside. Key Points: Detailed stratigraphy of lunar regolith on the Moon's farside is unveiled with Chang'E‐4 Lunar Penetrating Radar data The dielectric properties and ilmenite content of regolith materials at the landing region are identified The thickness and accumulated rate of lunar regolith at the landing region are constrained and analyzed